2011
DOI: 10.1016/j.ijgo.2011.03.018
|View full text |Cite
|
Sign up to set email alerts
|

A study of maternal mortality in 8 principal hospitals in Pakistan in 2009

Abstract: Maternal death can be effectively managed by skilled care during pregnancy, childbirth, and the postnatal period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Similar results were shown by Naheed Bano et al in 8 principal hospitals in Pakistan wherein out of the 108 maternal deaths in 2009, 78% died postnatally, 17.5% antenatally and 4.6% intranatally. 17 A study by Sahaja Kittur et al in Hubli showed that 75% deaths occurred in postpartum period. 18 Among the 90 maternal deaths, & died antenatally.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were shown by Naheed Bano et al in 8 principal hospitals in Pakistan wherein out of the 108 maternal deaths in 2009, 78% died postnatally, 17.5% antenatally and 4.6% intranatally. 17 A study by Sahaja Kittur et al in Hubli showed that 75% deaths occurred in postpartum period. 18 Among the 90 maternal deaths, & died antenatally.…”
Section: Resultsmentioning
confidence: 99%
“…The studies in Pakistan showed the rate between 3.9-6.3%, 11,12 with maternal mortality related to P-Sepsis was between 13-20%. [13][14][15] The available data in Pakistan is limited mainly hospital based data, the criteria of sepsis in also not clear. 16 This study showed that anemia was found in 63% of patients with sepsis, while other studies conducted in a public hospital showed, almost all suffering from anemia and one third of women hemoglobin was less 5g/dl with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, delivery of proper health care system and emergency obstetrical care facilities are vital for the prevention of PE/E [73]. Maternal mortality can be reduced with proper peripartum care [29] and skilled care during pregnancy, childbirth, and postnatal period [74]. Assessment of blood lipids is also helpful in the prevention of complications in patients with pregnancy-induced hypertension.…”
Section: Community-based Preventionmentioning
confidence: 99%